Case report of severe psychiatric sequelae in a 16-year-old female following resection of a purely dopamine-secreting ganglioneuroma. (2019) - Chai, Louis; Ciullo, Sean; Prasad, Rajeev
Highlights: Ganglioneuromas are rarely hormonally active. When metabolically active they typically secrete epinephrine or norepinephrine. Exclusively dopamine-secreting tumors are exceedingly rare. Surgical excision is the treatment of choice for ganglioneuromas. Psychiatric sequelae should be anticipated after resection of a purely dopamine-secreting tumor. Abstract: Background: Ganglioneuromas (GN) are rare, benign tumors derived from neural crest cells. They are in the same family of neuroblastic tumors that includes the intermediate ganglioneuroblastoma (GNB) and the malignant neuroblastoma (NB), each of which carries a different prognosis based on tumor histopathology. GNs are generally asymptomatic and usually found incidentally when the tumor becomes palpable or has grown large enough to exert mass effect on adjacent structures. Unlike their malignant counterparts, GNs are rarely hormonally active and usually do not exhibit systemic metabolic activity. We present a case of an adolescent female with a pelvic tumor that was found to be a purely dopamine-secreting GN. Resection resulted in sudden dopamine withdrawal and unexpected severe emotional lability post-operatively. Case: A 16-year-old female presented with a history of increasingly irregular menses over the past year and was found to have an 8-centimeter pelvic tumor. Subsequent work up revealed the mass to be solely dopamine secreting. The tumor was excised without preoperative hormonal blockade. Post-operatively, the patient developed severe emotional lability and symptoms of depression, likely related to the acute withdrawal of circulating dopamine. Conclusion: Ganglioneuromas are rarely metabolically active. However, a preoperative endocrine workup should be done to rule out other more commonly hormonally active tumors such as neuroblastomas, pheochromocytomas, and paragangliomas. If isolated dopamine secretion is found, hormonal blockade is not required preoperatively and operative manipulation and removal should be considered safe. However, one should anticipate potential emotional and psychiatric issues post-operatively due to the acute withdrawal of circulating dopamine.